The Effect Of Giving Exercise Of Passive Range Of Motion (ROM) To The Flexibility Of Knee Joint In Elderly: Subtitle : There is the Effect Of Giving Exercise Of Passive Range Of Motion (ROM) To The Flexibility Of Knee Joint In Elderly - Lumban Tobing, Martha Uli (Universitas Aufa Royhan, 2019)
As we get older, the flexibility of knee joint is decreases. Passive ROM exercise is an train to move joints as much as possible in a structured manner that is assisted by someone, and one of the benefits to increase flexibility. The purpose of this research was to determine the effect of passive ROM exercise to the flexibility of knee joint in elderly in the work area of the Batunadua Health Center in 2019. This research used a quasi experiment with a type of pre-test and post-test control group design. The sample used in this research was 32 elderly with 16 elderly for each experiment and control groups. Respondent selected by means of the elderly who entered the criteria. The result of this research through the paired T test statistical test showed a significant difference in the flexibility of knee joint in elderly before and after being given passive ROM exercise in the intervention and control group with p-value 0.000 < α (0.05). The experiment group increased whereas the control group experience decreased. The results of the statistical test using the independent t test on approved the flexibility of knee joint in elderly after the intervention in the experiment and control groups obtained a p-value of 0.009. This shows that there is a significant difference between the flexibility of knee joint in elderly of the experiment and control groups. ROM exercises on a regular basis, it will make the joint space move so that the degree of flexibility increases and allows it to return to the normal range.